Respons Perilaku Pasar Terhadap Teknologi Informasi di Indonesia dalam Tinjauan Ekonomi Islam - Haryono Haryono; Hasnil Hasyim (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2021)
The market behavior response to the rapidly growing information technology in Indonesia is forcing the market to adapt quickly. In the digital era 4.0, there have been quite extreme changes in business models. Even the giant companies have gone out of business. In the perspective of Islamic economics this phenomenon continues to be studied. In one condition, business growth is growing very fast and on the other hand the fatwas of the ulama are often left behind. This qualitative research is presented with a phenomenological approach and sharia compliance. The data analyzed are secondary data related to the latest facts about the information technology market. The author uses the theory of market behavior change to strengthen this argument. In principle, Islam always gives appreciation to technological developments that aim to facilitate human work, as long as these facilities do not violate the forbidden boundaries. In the perspective of Islamic economics, the focus is on the business schemes that are run and the muamalah contracts that are used whether they meet the requirements and pillars or not. If the conditions and pillars are met then the business can be run. Simply put, please do business using advanced technology but still comply with sharia principles.